Isopod assemblages in the Bizerte lagoon (SW Mediterranean Sea): composition, structure and environmental relationships - KHAMMASSI, MARWA; JOURDE, JEROME; LABIDI, SARRA; ACHOURI, MOHAMED SGHAIER (Mediterranean Marine Science, 2022)
The spatial and temporal distribution, abundance, and structure of isopod assemblages in Bizerte Lagoon (SW Mediterranean Sea) were studied at 22 stations selected from seagrass and macroalgae sampled during four seasons in 2017. A total of 6808 individuals and 17 species of isopods belonging to 5 suborders, 7 families and 12 genera were identified. Six new species were recorded on Tunisian coasts. In addition, and compared to previous studies, nine isopod species were collected for the first time in this lagoon. Analysis of the trophic structure revealed that most stations are strongly dominated by herbivore-deposit feeders (78.3%), followed by deposit-suspension feeders (13.6%) and carnivores (8.01%). Three isopod assemblages were identified (G1, G2 and G3). The distribution of isopod assemblages is influenced by the nature and structure of the substrates. The seasonal variations in the isopod community patterns at 22 stations showed maximum abundance and diversity during spring, whereas the lowest ones were recorded during winter.